Tantangan Pembelajaran, Tingkat Stres dan Koping Stres Mahasiswa Kebidanan Di Wilayah Kota Padang - Hindun Mila Hudzaifah; Feri Anita Wijayanti; Dilla Dwi Tilana; Rizki Indriana Wulan Savitri (Jayapangus Press, 2026)
Higher education life with adjustments to the campus environment can trigger stress on students. College students are a group of individuals who are prone to experiencing homeostatic imbalances due to stress that comes from academic demands. The type of research used in this research is an analytic survey with a cross approach-sectional. The research location is the Midwifery Institute in Padang City. The population in this study were all midwifery students who had attended clinical clerkships in practice areas such as hospitals, health centers and midwifery independent practices. In this study, the sampling technique used is the sampling method consecutive sampling with a sampling determination technique in which all subjects who come and meet the selection criteria are included in the study until the required number of subjects is met. Based on the results of the research that has been done, the results show that there is an intermediate effect coping strategies to psychological distress in midwifery students in the city of Padang. By type coping, type emotional focused coping and avoidance coping influence psychological distress, where as problem focused coping not found to affect psychological distress. Emotional focused coping and avoidance coping is a form coping strategies most used by students against psychological distress experienced.